Profil Bahan Organik Pada Air di Bagian Hilir Sungai Jangga, Kabupaten Karangasem, Bali. - Sunaryuga, I Gede Duta; Perwira, Ima Yudha; Negara, I Ketut Wija (Current Trends in Aquatic Science; Vol 7 No 1 (2024), 2024)
Jangga river is one of the major rivers that pass through Karangasem Regency. The Jangga river flows from the Padangkerta Village (upstream), the Subagan Village and ends in the Tumbu Village at the downstream. Organic matter has an important role for the productivity of water ecosystems. The accumulation of organic matter in the mouth of the river can threaten the ecological system and reduce the quality of the river waters. This study aims to determine the level of pollution and water quality in the Jangga River, Karangasem, Bali. The method used in this study is a quantitative descriptive method. Parameters measured were BOT, ammonia, TSS, TDS, DO, pH, temperature and turbidity. The results showed that the condition of the waters in the Jangga River in general is still classified as unpolluted according to Government Regulation Number 22 of 2021, concerning the implementation of environmental protection and management.